(untitled) (Gestão & Regionalidade, 2016)
This study aimed to analyze the perception scenarios of two businessmen from the construction materials industry in the city of Toledo, west of Paraná state, Brazil, through Porter’s Five Forces model and SWOT analysis. It was made a thematic content analysis of two semi-structured interviews, using for this purpose the ATLAS.ti software. This study allowed demonstrating that both of them had a realistic and optimistic outlook about future scenarios in the construction materials business in the city of Toledo, which is different from the pessimistic outlook that is evolving in the economic environment and national politics. It is important to note that, in both cases, this view is confirmed due to the perception that the regional economy based on the agribusiness and the pharmaceutical industry has not been directly affected by the crisis yet.